Analysis of Brawijaya University Academic Information Systems Acceptance on the User Characteristic, System Quality, Support of Top Management and Information Technology, Perceived Usefulness, and Perceived Ease of Use - Mursityo, Yusi Tyroni (Faculty of Computer Science (FILKOM) Brawijaya University, 2018)
Sistem Informasi Dosen (SIADO) as an academic information system for Universitas Brawijaya lecturers are not fully optimized and used since many perspectives about the system, such as system quality complaints and it’s not obligated to use by the University leaders even many benefits can be obtained. This research conducted to describe the factors on SIADO’s user acceptance in five variables, namely is user characteristic, system quality, top management & IT support, perceived usefulness, and perceived ease of use, using descriptive statistical analysis. Data collection techniques with offline questionnaire were distributed using paper from 96 Universitas Brawijaya lecturers. Validation and reliability were checked with statistics methods and descriptive statistical analysis is implemented to measure the level of categories on each variable to provide calculation and information based on data centralization and dissemination, and acquired categorized data. The results show that all five variables receive high category on SIADO acceptance, which indicates the user perception all five variables are good to be used as a consideration tool in receiving the actual use of the system.